Enhanced Condensation on Soft Materials through Bulk Lubricant Infusion. (29th December 2021) - Sharma, Chander Shekhar; Milionis, Athanasios; Naga, Abhinav; Lam, Cheuk Wing Edmond; Rodriguez, Gabriel; Del Ponte, Marco Francesco; Negri, Valentina; Raoul, Hopf; D'Acunzi, Maria; Butt, Hans‐Jürgen; Vollmer, Doris; Poulikakos, Dimos
Abstract: Soft substrates enhance droplet nucleation during water vapor condensation because their deformability inherently reduces the energetic threshold for heterogeneous nucleation relative to rigid substrates. However, this enhancement is counteracted later in the condensation cycle, when substrate viscoelastic dissipation inhibits condensate droplet shedding. Here a polydimethylsiloxane (PDMS) based organogel is designed to overcome this limitation. It is shown that merely 5% bulk lubricant infusion in PDMS reduces viscoelastic dissipation in the substrate by nearly 28 times while doubling the droplet nucleation density. Parameters for water condensation on this organogel are correlated with material properties controlled by design, i.e., fraction and composition of uncrosslinked chains and shear modulus. It is demonstrated that the increase in nucleation density and reduction in precoalescence droplet growth rate is rather insensitive to the lubricant percentage in PDMS within the broad range investigated. These results indicate the presence of a lubricant layer on the substrate surface that cloaks the growing condensate droplets. This cloaking effect is visualized, and it is shown that cloaking occurs significantly faster on PDMS if it is infused with bulk lubricant. Overall, bulk lubricant infusion in PDMS enhances condensation and leads to a more than 40% higher dewing on the substrate. Abstract : Polydimethylsiloxane (PDMS) based organogel is designed through bulk lubricant infusion to simultaneously improve nucleation density ( N ) and droplet‐shedding rate during water condensation. The added lubricant increases the fraction of uncrosslinked chains ( W ), significantly reduces viscoelastic braking (higher droplet sliding velocity, U drop ), and cloaks condensed droplets while doubling N . The organogel achieves >40% increase in dewing compared to PDMS without lubricant.